INTERPRETATION OF THE QURAN IN ONLINE MEDIA - Hamdan Yuwapini; Ziyad Ulhaq; Samsul Ariyadi (PT. Jurnal Center Indonesia Publisher, 2025)
The discussion of interpretation in online media today does not only cover the transition from print media to digital media, but can also include the development of direct interpretation studies. This reflects the diversity of approaches and perspectives in the discussion of interpretation on the internet today . This writing aims to identify ways the study and presentation and approaches applied to the study of interpretation are very diverse website tafsirq.com , and to understand the dominant interpretation ideology on this website . in explaining questions related to the study of interpretation on this website . This research applies descriptive-analytical method. This method is used to study and analyze sources on the study of interpretations available on the tafsirq.com website , with the aim of providing a clear and detailed picture of the interpretive approaches and ideologies used on the site. Presentation in site Tafsirq.com in data display, there are displays such as the Qur'an, the Medina mushaf, stories of wisdom, prayers, and recitations per verse, also equipped with the DSN Fatwa. on the Tafsirq.com site , there are two tafsir books Which use with discussion method​ use title (topic). This site is said to be credible because on its website , the administrator displays responsible for content and in interpreting the verses I have referred to the famous tafsir books from the Tafsir Al-Misbah and Tafsir Jalâlīn .